A novel bio-psycho-social approach for rehabilitation of traumatized victims of torture and war in the post-conflict context: a pilot randomized controlled trial in Kosovo. Issue 1 (December 2016) - Wang, Shr-Jie; Bytyçi, Ardiana; Izeti, Selvi; Kallaba, Melita; Rushiti, Feride; Montgomery, Edith; Modvig, Jens
Abstract Background Some evidence showed that multidisciplinary rehabilitation in Western countries is effective for treating war-related trauma, but it remains unclear whether this approach is applicable to civilians living in resource-poor countries affected by war. In 2012–14, Danish Institute against Torture (DIGNITY) conducted a randomized controlled trial (RCT), in partnership with Kosova Rehabilitation Centre for Torture Victims (KRCT), to examine the effects of multidisciplinary intervention among victims of torture and war in Kosovo. Methods A single-center, randomized, parallel-arm, single-masked, waiting-list controlled trial was implemented in northern Kosovo. Thirty-four participants meeting the recruiting criteria were randomized to either intervention group, which received integrated treatments plus a once-daily multivitamin, or the waiting list group, which received multivitamin alone. The integrated treatments consisted of 10 weekly individual 60-min sessions of cognitive behavioral therapy (CBT), based on an adapted prolonged exposure therapy manual, an individual 20-min breathing exercise with an emWave biofeedback device, and 90-min group physiotherapy. The waiting list group also received the same treatment after the intervention group had completed their sessions. Outcome assessments were conducted at 3, 6 and 9 months after baseline assessment. Outcomes measures consisted of 4 subtypes: mental, emotional, physical health, functioning and social outcomes, i.e. PTSD, depression, anxiety, chronic pain, anger and hatred expression, body mass index, handgrip strength, standing balance, income, employment rate and disability score. Results Over 1/3 of PTSD cases were successfully treated. Inconsistent patterns with mental health and chronic pain outcomes were observed while there was a definite impact of intervention on functioning and social outcomes, i.e. the employment rate, which increased nearly 15 %, and the monthly wage, which rose 45–137 %. There was also a noticeable improvement in handgrip strength and disability score; the feelings of anger and hatred diminished. However, most of these changes did not reach statistical significance. Conclusions The impact of bio-psycho-social intervention is likely sensitive to the context of post-war economy in Kosovo and the treatment goals. The potential for improving the emotional well-being and employment outcome in victims was demonstrated. A larger scale RCT in a similar setting is needed, with close monitoring of treatment integrity and data reliability. Trial registration Clinicaltrials.gov (NCT01696578 ).